Ultra‐fast, low‐cost, and green regeneration of graphite anode using flash joule heating method - Dong, Shu; Song, Yali; Ye, Ke; Yan, Jun; Wang, Guiling; Zhu, Kai; Cao, Dianxue (EcoMat (Beijing, China), 2022)
Graphite is the state‐of‐the‐art anode material for most commercial lithium‐ion batteries. Currently, graphite in the spent batteries is generally directly burned, which caused not only CO2 emission but also a waste of precious carbon resources. In this study, we regenerate graphite in lithium‐ion batteries at the end of life with excellent electrochemical properties using the fast, efficient, and green Flash Joule Heating method (FJH). Through our own developed equipment, under constant pressure and air atmosphere, graphite is rapidly regenerated in 0.1 s without pollutants emission. We perform a detailed analysis of graphite material before and after recovery by multiple means of characterization and find that the regenerated graphite displays electrochemical properties nearly the same as new graphite. FJH provides a large current for defect repair and crystal structure reconstruction in graphite, as well as allowing the SEI coating to be removed during ultra‐fast annealing. The electric field guide the conductive agent and binder pyrolysis products to form conductive sheet graphene and curly graphene covering the graphite surface, making the recycled graphite even better than new commercial graphite in terms of electrical conductivity. Regenerated graphite has excellent multiplier performance and cycle performance (350 mAh g−1 at 1 C with a capacity retention of 99% after 500 cycles). At cost, we get recycled graphite that displays the same performance as new graphite, costing just 77 CNY per ton. This FJH method is not only universal for the regeneration of spent graphite generated by various devices but also enables multiple use‐failure‐regeneration steps of graphite, showing great potential for commercial applications. The regeneration of the spent graphite can be realized by FJH treatment, and the performance of the regenerate graphite can be comparable to the new commercial graphite, which realizes the rapid and environmental recycling of the spent anode, and greatly reduces the material cost.